2009
DOI: 10.2214/ajr.08.1434
|View full text |Cite
|
Sign up to set email alerts
|

Freehand Versus Guided Breast Biopsy: Comparison of Accuracy, Needle Motion, and Biopsy Time in a Tissue Model

Abstract: Biopsy using the developed needle guidance system is feasible and its use decreases procedure time and decreases needle motion; thus, it has the potential to reduce patient morbidity. Moreover, less operator experience is required for a successful breast biopsy using the needle guidance system than using the freehand technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…According to Memel et al, 8 the major challenge to performing a safe biopsy is real‐time needle visualization. Commercially available sonographic guides, which have a fixed angle, are inexpensive alternatives that may provide more confidence regarding the needle position inside the body when performing sonographically guided proce‐dures 2 due to the predetermined track of the needle based on the guide's angle line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Memel et al, 8 the major challenge to performing a safe biopsy is real‐time needle visualization. Commercially available sonographic guides, which have a fixed angle, are inexpensive alternatives that may provide more confidence regarding the needle position inside the body when performing sonographically guided proce‐dures 2 due to the predetermined track of the needle based on the guide's angle line.…”
Section: Discussionmentioning
confidence: 99%
“…The two commonly used methods are the freehand and needle‐guided techniques. The guided technique depends on a fixed angle between the needle trajectory and the ultrasound probe 2 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the free-hand technique requires more operator expertise to see the needle tip in the ultrasound image. 17 In our study, identification of the interspace level by palpation rather than by ultrasound differed in only two of the 19 subjects. However, since previous studies 3 have suggested that palpation misidentifies the actual space in 58% of the cases, it is recommended that ultrasound guidance continue being used.…”
Section: Discussionmentioning
confidence: 54%
“…[32] In the literature on simulation-based training, similar bench models made from chicken parts postmortem have been previously used with different indications, such as legs for teaching how to change needle angles, microneurosurgical and microvascular surgery and bedsidedetection of glass in wounds;[3335] thigh, wings, esophagus and trachea for microsurgical surgery training;[3640] the gizzard, posterior trunks, crop and esophagus for laparoscopic training;[4143] and others. [44-45]…”
Section: Discussionmentioning
confidence: 99%